Phytochemical Screening Mango Bacang Leaf Extract (Mangifera foetida L) and Salam Leaf Extract (Syzygium polyanthum) - Kony Putriani; Syahral Ramadhani; Melanie Amalia Fitry; Suyefri Sony; Amelia Wulansari (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2021)
Bacang mango leaves and bay leaves are plants that have been used for a long time, even bay leaves themselves are often used as cooking ingredients. Mango Bacang leaves and bay leaves contain alkaloids, phenols, tannins, flavonoids, steroids, saponins, triterpenes, polyphenols as well as essential oils. So this research was conducted to develop the use of mango Bacang leaves and bay leaves as natural medicine. The sample was determined and identified in the laboratory of the Faculty of Mathematics and Natural Sciences, Riau University. Furthermore, the mango Bacang and bay leaves were macerated using 96% ethanol and extracted until a thick extract was obtained which would then be tested for phytochemical screening on the Bacang mango leaf extract and bay leaf extract. The results obtained that the extract of mango Bacang leaf and bay leaf extract were positive for containing flavonoid compounds, saponins and tannins so that they could be developed to be used as natural remedies.